Indoor visible light positioning system on Android smartphone - Manickam, Yuvaraj (2019)
In this dissertation, an indoor visible light positioning (VLP) system using general LED lamps, the smartphone front camera is set up, investigated and implemented in the Android phone using the programming language of Java. With the support of external library functions such as OpenCV, graphView, and Jama, I have developed an application which is able to locate and display the position of the user by sequential means of 1) image capture, 2) image processing and contour detection, and 3) numerical calculations of scaling factors, rotation matrix as well as translation matrix. I have also designed the user interface with necessary prompts and error messages. The application is user-friendly as it is simple and easy to use. Real-time experiments are carried out to experimentally evaluate the performance of the indoor positioning in terms of its accuracy and robustness. A test bed of 2m height has been set up in the laboratory for a single VLP unit. The results show that the 3D positioning accuracy of 8 cm can be achieved. In this project, the positioning error (PE) and the performance of the optimized VLP system will be explained in detail. This dissertation achieves smartphone based real-time indoor 3D positioning of high robustness and accuracy.